Rehabilitation and Return to Sport After Arthroscopic Treatment of Femoroacetabular Impingement: A Review of the Recent Literature and Discussion of Advanced Rehabilitation Techniques for Athletes - Mark J. Holling, P.T., D.P.T; Scott T. Miller, P.T., M.S., S.C.S., C.S.C.S; Andrew G. Geeslin, M.D (Elsevier, 2022)
The purpose of the article is to present an updated literature review, as well as describe our approach to rehabilitation and return to sports following hip arthroscopy for femoroacetabular impingement (FAI) with labral repair. A literature review was performed to identify articles published within the last 10 years that were focused on this topic. Relevant articles were reviewed, and reference lists were searched to identify additional articles. Findings were summarized for rehabilitation phases and return-to-sports assessment. Additionally, advanced rehabilitation topics are reviewed. Several systematic reviews and individual case series were identified. There is relative uniformity concerning the use of a four-phase approach for rehabilitation. However, there is inconsistency in terms of timing and criteria for ultimate return to sport. Advanced rehabilitation topics were reviewed, and description of their relevance at various rehabilitation phases was provided. A four-phase approach to rehabilitation following hip arthroscopy for FAI is widely used with general uniformity, although the timing and level of detail concerning assessment and readiness for return to sport are variable. Advanced rehabilitation techniques may be used in select patients returning to high-level activities.